2017
DOI: 10.19030/jabr.v33i2.9900
|View full text |Cite
|
Sign up to set email alerts
|

After-Hours Block Trading, Short Sales, And Information Leakage: Evidence From Korea

Abstract: We investigate the impact of insider trading in after-hours block market on stock price and short sales volume, before and after the trading becomes public information. During pre-announcement period, positive (negative) abnormal stock return is generated when insiders buy (sell) their shares but does not when quasi-insiders trade, implying that stock price reflects long-lived private information of corporate governance structure. The impact is most prominent when ownership shares are transferred to (from) cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In prior literature related to off-hours block trading, Khil et al (2005) provided indirect evidence of information leakage using the closing price on the trading day. Moreover, Lee and Jun (2017) concluded that pre-disclosure information was leaked by insiders. This study investigated information leakage by block traders acting as agents for activating stock trades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior literature related to off-hours block trading, Khil et al (2005) provided indirect evidence of information leakage using the closing price on the trading day. Moreover, Lee and Jun (2017) concluded that pre-disclosure information was leaked by insiders. This study investigated information leakage by block traders acting as agents for activating stock trades.…”
Section: Discussionmentioning
confidence: 99%
“…Khil et al (2005) suggested that the closing price of the stock on the block trading day reflected private information regarding the impending trade to which Pre-disclosure information leakage block traders had access. In addition, Lee and Jun (2017) found that off-hours block trading executed by insiders was related to a leakage of information prior to public disclosures. Brunnermeier (2005) found that early-informed investors could exploit pre-disclosure private information twice: once before the disclosure and once after the disclosure.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation